2008
DOI: 10.1002/jtr.646
|View full text |Cite
|
Sign up to set email alerts
|

Which type of tourism matters to the regional economic growth? The cases of Spain and Italy

Abstract: Recently, the attention given to the importance of tourism in economic growth has significantly increased. However, research in this area mainly refers to international tourism and to the national level. This paper focuses on the influence of tourism on the economic growth of Spanish and Italian regions. Both international and domestic tourism are analysed and geographical location criteria are considered. Dynamic panel data techniques are applied. The results reveal that both international and domestic touris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(77 citation statements)
references
References 32 publications
5
68
0
4
Order By: Relevance
“…This phenomenon has also occurred in other sun and beach resorts created in the 1960s by the LC&NTIA on the Spanish coast, becoming mature destinations since the decade of the 1990s. The methodology used allowed a diagnosis of their status as a market product; this analysis could also even be extrapolated to regions in other countries of the European coastline with similar boundary conditions, such as France or Italy (Cortes‐Jimenez ).…”
Section: Discussionsupporting
confidence: 84%
“…This phenomenon has also occurred in other sun and beach resorts created in the 1960s by the LC&NTIA on the Spanish coast, becoming mature destinations since the decade of the 1990s. The methodology used allowed a diagnosis of their status as a market product; this analysis could also even be extrapolated to regions in other countries of the European coastline with similar boundary conditions, such as France or Italy (Cortes‐Jimenez ).…”
Section: Discussionsupporting
confidence: 84%
“…Spain seems to have a stronger international tourism sector than Italy over decades and even nowadays seems to experience an ongoing expansion. Cortés-Jiménez (2008) showed that for the period 1990 -2004 international arrivals in Italy raised by 47% in contrast to 88% in Spain, while the domestic arrivals in Italy grew by 9% in contrast to 75% in Spain. These figures show a different scenario for each country and further support the heterogeneous results achieved by the empirical analysis.…”
mentioning
confidence: 89%
“…Other studies are based on neoclassical economic growth theory and the augmented Solow model, including tourism proxies as a separate input factor or international inbound tourism as a component of exports into this model, which is rather questionable. Finally, most previous studies only analyze the relationship between international tourism and economic growth, which neglects the contribution of domestic tourism to economic growth (Cortés-Jiménez, 2008). Apart from the data unavailability problem, another reason for omitting domestic tourism is that its effect on economic growth cannot be explained by the TLG hypothesis framework or as part of international trade.…”
Section: Tourism and Economic Growth: Concepts And Measurementmentioning
confidence: 99%